A free account or not? Its effect upon information yield in strategic interviews with suspects. Issue 3 (19th September 2022) - van Beek, Martijn L. J.; Bull, Ray; Mijalkovic, Suzana
Abstract: Asking suspects for a free account (FA) at the start of an interview is considered good practice in a growing number of police organisations, whereas in others it still is not commonplace. This study explored whether interviews with or without such an invitation yielded more information from guilty suspects. Students in safety and security committed a mock crime and were then interviewed using a strategy of gradual disclosure of evidence, in the experimental condition preceded with an FA invitation ( n  = 20) and without such an invitation in the control condition ( n  = 17). On average, relatively little information was collected in the FA phase and far more in the subsequent gradual disclosure phase. However, the FA condition yielded seven confessions, four of which were given already in the FA phase. The No FA condition yielded only two confessions. Other differences in yield were not found. These findings indicate that an FA invitation could lead to some relevant and important information, such as a confession, being gathered already at an early stage of an interview, and that such an invitation does not hamper the gathering of further information later in the interview.